(untitled) (Divya Gyan Journal of Business and Computing, 2026)
Excessive computational and memory requirements associated with traditional full-fine tuning, despite their remarkable performance, significantly hinder the pragmatic application of modern vision transformers especially for histopathological image analysis. To alleviate this problem, modern transformers like Swin and DeiT are systematically evaluated using Low Rank Adaption (LoRA) technique, which is a parameter efficient fine-tuning technique, especially designed to shorten training time in natural language processing. When LoRA is applied to histopathological image classification, surprisingly, LoRA adapted Swin and DeiT models performs comparable performance across all evaluation metrics: accuracy, precision, specificity and F1 score, compared to their full- fine-tuned counterparts by updating less than 2% of the model’s parameters. The results show that LoRA not only accelerate training speed by updating fewer than 2% of the model’s parameters but also achieves superior accuracy for both Swin (99.42% vs. 99.21%) and DeiT (99.27% vs. 98.91%) compared to their fully fine-tuned counterparts on NCT-CRC-HE dataset. Consequently, efficient fine-tuning using LoRA can provide an alternative way to traditional full fine-tuning without scarifying performance while boosting training speed, opening new avenues for various medical image classification problems.